Analisis kebutuhan modul pembelajaran keterampilan menulis teks deskripsi berwawasan kebinekaan global - Widhiyanto, Riyadi; Zulaeha, Ida; Wagiran, Wagiran (Universitas Mulawarman, 2024)
Writing skills in Indonesian are still a major challenge in learning. The focus of attention includes the need for more clarity of material, the lack of writing activities, and students' difficulty in determining topics and developing ideas. This study aims to analyze the need for developing a learning module for writing description texts with an insight into global diversity. The research method used was Mix Methode Research (MMR) involving 97 students and 6 educators in junior high school. Data were collected through questionnaires, interviews, and documentation studies. Data analysis was done by quantitative and qualitative analysis. The study's results, first, the learning process of writing description text has yet to be achieved optimally. This is due to the lack of teaching materials and the need for students' writing activities. Second, the quality of teaching materials used in the learning process has yet to meet the material needs in accordance with the learning outcomes. Third, the character value of global diversity is one of the opportunities to be integrated with the learning process of writing description text.